Healthcare judicialization: an analysis of indicators and official data on medications - Nádia Bernardinis; Vanessa Terezinha Gubert; Cristiane Munaretto Ferreira; Jorge Otávio Maia Barreto (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to analyze judicial demands for medications in Campo Grande, Brazil, between July 2018 and June 2020. Methods: the four dimensions of the Manual of Indicators for Evaluation and Monitoring of Judicial Demands for Medications were examined. Results: 676 judicial processes were identified, corresponding to 1006 requests for 284 different medications. In 92.74% of the processes, access to medications was granted, with 88.80% granted on an urgent basis. The median time between the decision and delivery of the medication was 146 days. The average monthly cost of acquiring medications was R$ 2,183.68 Brazilian reais. Among the identified medications, 90.22% had at least one therapeutic alternative available in the public healthcare system. Conclusions: characterizing and analyzing judicial demands related to medications can support discussions on updating medication lists and clinical protocols, organizing healthcare services, allocating resources, and implementing actions to reduce judicialization.